Pesan Moral dalam Film Ada Mertua di Rumahku di KlikFilm (Analisis Semiotika Roland Barthes) - Rasendra, Keefe; Soraya, Iin; Muntazah, Arina (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
Film is a medium that can reflect social reality in everyday life and participate in the creation of reality. The Indonesian movie that airs on KlikFilm service entitled Ada Mertua di Rumahku displays social reality, namely about the life of a married couple with their father-in-law. A movie can convey various messages, one of which is a moral message. Given that a movie can be adapted from a novel or true story to describe someone's life story. These messages are very important in influencing changes in audience behavior. The purpose of this study is to determine the content of moral messages in the movie Ada Mertua di Rumahku. This research uses descriptive qualitative method by observing the scenes of the movie Ada Mertua di Rumahku. The data in this study were analyzed using Roland Barthes Semiotics which uses two-stage signification, namely denotation and connotation as well as myths in capturing scenes in the film Ada Mertua di Rumahku. The results of this study indicate the existence of moral messages which include the categories of moral messages about Marriage, Filial Piety, Patience, and Compassion.